Barriers To Women's Leadership Positions In Palestinian Government Universities - Eman I.Issa; Is'haq Ibrahim Ahmad Bani Melhem (HRMARS, 2024)
International Journal of Academic Research in Business and Social Sciences Volume 13 No 2 Page (1411-1420)